2018
DOI: 10.1111/jocn.14326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multicomponent interventions on competence of family caregivers of people with dementia: A systematic review

Abstract: The competence of family caregivers is essential for the life quality of PwD. To promote the health of the family caregiver and PwD, multicomponent interventions may be appropriate for nurses to practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…At the same time, 20 articles provided negative or mixed reviews. These included reviews on psychoeducation [12,23,58,62,70], CBT-based psychotherapeutic interventions [37], mindfulness [43], support interventions [12,24,62], respite [65,66], home care [56], physical activity interventions [70], multicomponent interventions [12,70,72], dyadic interventions [40,60], technology-based interventions [25,26,42,64,68], and miscellaneous (e.g., physical activity, dyadic) interventions [40,67,70]. Note that the same article might have provided both positive and negative reviews, depending on the intervention category concerned.…”
Section: Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, 20 articles provided negative or mixed reviews. These included reviews on psychoeducation [12,23,58,62,70], CBT-based psychotherapeutic interventions [37], mindfulness [43], support interventions [12,24,62], respite [65,66], home care [56], physical activity interventions [70], multicomponent interventions [12,70,72], dyadic interventions [40,60], technology-based interventions [25,26,42,64,68], and miscellaneous (e.g., physical activity, dyadic) interventions [40,67,70]. Note that the same article might have provided both positive and negative reviews, depending on the intervention category concerned.…”
Section: Burdenmentioning
confidence: 99%
“…By mastery, we refer to several interrelated constructs including ability, sense of competence and self-efficacy, which altogether were covered by 13 reviews. Eight reviews concluded that certain interventions could enhance mastery, including psychoeducation [51,53,66], OT interventions [16,66], multicomponent interventions [72], technology-based interventions [17,51], and miscellaneous/general interventions [35,53,61]. Five other reviews, however, found no effect of psychoeducation [62], technology-based interventions [26,42,46], or miscellaneous interventions [67].…”
Section: Masterymentioning
confidence: 99%
“…2,7 Evidence has shown that appropriate multicomponent interventions which include psycho-education, training and support can significantly reduce caregiver burden and improve well-being and competence of caregivers. [8][9][10][11] However, most of these studies have been conducted in high-income countries and the interventions are typically time-intensive and require trained health personnel such as psychologists, therapists or medical doctors. [12][13][14] In India, a home based support intervention was found to be effective in reducing caregiver burden and promoting caregiver mental health, but required the involvement of psychiatrists, counselors and community volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that appropriate multicomponent interventions which include psycho‐education, training and support can significantly reduce caregiver burden and improve well‐being and competence of caregivers 8–11 . However, most of these studies have been conducted in high‐income countries and the interventions are typically time‐intensive and require trained health personnel such as psychologists, therapists or medical doctors 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…And above all, it is preferred by most patients with dementia [31][32][33]. The competence of caregivers is essential for the life quality of patient with dementia, and multicomponent interventions may be appropriate for nurses to practice [34].…”
Section: Needs and Demands Socio-health Of The Patientsmentioning
confidence: 99%